Mikroprosesor Intel: Arsitektur, Pemrograman dan Antar Muka 8086/8088,80186/80188,80286,80386,80486,Pentium, Prosesor Pentium Pro, Pentium II, Prntium III, dan Pentium 4 - Jilid II - Brey, Barry B. (Andi, 2003)
x, 333 hlm.; ilus.; 27 cm